Framing of economic news and policy support during a pandemic: Evidence from an information experiment - Patrick Bareinz; Fabian Koenings (Friedrich Schiller University Jena, 2021)
We investigate the effect of how news outlets communicate macroeconomic information to consumers on support for governmental policy in the context of the COVID-19 crisis. In our survey experiment based on a representative sample of 3000 individuals in Germany, respondents are exposed to an expert forecast of GDP growth. Individuals are randomly assigned to either receive no information, the baseline forecast information, or real-world frames of the same information used in newspaper articles on the topic. We find that in contrast to the baseline information, positive framing of forecasted economic growth by news outlets increases support for pandemic policy. This effect is especially pronounced for respondents with more pessimistic macroeconomic expectations. Further evidence suggests that negative economic news are perceived as more credible and hence less surprising in times of recession, not translating into a change in political opinion.
Keywords: C90; D83; D84; D91; 330; expectation formation; information experiment; media framing; macro economic information; policy support; COVID-19 crisis